الإصلاح الدستوري في تونس بعد 2011: السياقات والرهانات الجديدة - زروال, سهام (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
Constitutional reform is one of the basic entrances that would achieve political reform in many countries, especially after the democratic transformation experiments demonstrated the importance of constitutions in building the edifice of institutionalized state or input a new social and political contract, Tunisia, is among those countries wheat has witnessed social, political and constitutional dynamics since the decades, but the constitutional engineering after revolution of the 14 january 2011, which requires us to identify the different contexts and new challenges that are made during the drafting of the new constitution, as well as the identification of the various implications, those relating to the rebalancing of powers and put a break with the former Constitutional system whith its authoritarianism nature.